2015
DOI: 10.1021/acs.orglett.5b03223
|View full text |Cite
|
Sign up to set email alerts
|

An N-Heterocyclic Carbene-Catalyzed Oxidative γ-Aminoalkylation of Saturated Carboxylic Acids through in Situ Activation Strategy: Access to δ-Lactam

Abstract: An N-Heterocyclic Carbene (NHC)-catalyzed oxidative formal [4 + 2] annulation of acylhydrazones with saturated carboxylic acids bearing γ-H to assemble δ-lactams featuring a chiral carbon stereogenic center was developed through an in situ activation strategy. The ready availability of the starting materials, excellent enantioselectivity, facile assembly, high yields, and potential biological significance of the final products make this protocol an attractive alternative for the construction of the pyridinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…In 2015, Yao et al. reported NHC‐catalyzed oxidative formal [4+2] annulation of acylhydrazones with saturated carboxylic acids bearing γ‐H for the synthesis of these compounds [14] . In 2021, Glorius reported the synthesis of enantiornitine δ‐lactams using hydrogenation of oxazolidinone‐substituted pyridines [15] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Yao et al. reported NHC‐catalyzed oxidative formal [4+2] annulation of acylhydrazones with saturated carboxylic acids bearing γ‐H for the synthesis of these compounds [14] . In 2021, Glorius reported the synthesis of enantiornitine δ‐lactams using hydrogenation of oxazolidinone‐substituted pyridines [15] .…”
Section: Methodsmentioning
confidence: 99%
“…[13] In 2015, Yao et al reported NHC-catalyzed oxidative formal [4 + 2] annulation of acylhydrazones with saturated carboxylic acids bearing γ-H for the synthesis of these compounds. [14] In 2021, Glorius reported the synthesis of enantiornitine δ-lactams using hydrogenation of oxazolidinonesubstituted pyridines. [15] In the same year, McNaughton and Rovis reported asymmetric δ-lactam synthesis using metalloenzyme catalyzed enantioselective tandem CÀ H activation and [4 + 2] annulation reaction.…”
mentioning
confidence: 99%
“…In 2015, Yao and co-workers employed a novel approach for the synthesize δ-lactams 18 possessing chiral carbon from NHCcatalyzed oxidative [4 + 2] annulation of saturated carboxylic acids 16 possessing γ-hydrogen with acylhydrazones 17 by in situ activation approach (Scheme 4). [22] The authors proposed the following mechanism as shown in scheme 5. Activating agent HATU (Hexafluorophosphate Azabenzotriazole Tetramethyl Uronium; IUPAC name: Chi and co-workers carried out the asymmetric synthesis of lactams 28 from inert β-sp 3 carbon of a saturated esters 26 with enamine precursor 27 employing NHC catalysis (Scheme 6).…”
Section: Lactamsmentioning
confidence: 99%
“…Yao et al. berichteten 2015, dass Azoliumdienolat‐Intermediate durch oxidative NHC‐Katalyse auch aus gesättigten Carbonsäuren erhalten werden können . Verschiedene gesättigte Carbonsäuren 52 reagierten mithilfe von C‐12 als Präkatalysator und HATU gut mit den Hydrazonen 46 zu den δ‐Lactamen 47 (Schema ).…”
Section: [4+2]‐cycloadditionen Von Azomethinverbindungenunclassified